Oral, not gut microbiota diversity, reflects the inflammation and neoplasia in patients with uveitis and vitreoretinal lymphoma - Michaela Brichova; Lucie Dlouha; Marketa Tenglerova; Johana Rehakova; Martin Kostovcik; Katerina Benesova; Stepan Coufal; Eliska Pivrncova; Zuzana Jiraskova Zakostelska; Miloslav Kverka; Eva Skrlova; Petra Svozilkova; et al. (Journal of Ophthalmic Inflammation and Infection)
Abstract Purpose Dysregulation of the microbiota on different mucosal surfaces is associated with both immune-mediated and malignant diseases. Nevertheless, the involvement of different microbial communities is still poorly characterized. The aim of our study was to compare oral and gut microbiota composition between patients with uveitis, vitreoretinal lymphoma (VRL), and controls. Methods This study was designed as a prospective observational study. The inclusion criteria were treatment-naïve patients with immune-mediated uveitis or newly diagnosed VRL. The buccal swab and faecal samples were collected and bacterial 16S ribosomal RNA gene sequencing was used to identify the oral and gut microbiota. Results We enrolled 18 patients with uveitis, median age 39 years, 16 patients with VRL, median age 67.5 years, and 16 controls, median age 63 years. In the oral microbiota, the patients suffering from uveitis showed significant enrichment of genera Pseudomonas (p < 0.0001 and p < 0.0001), and Diaphorobacter (p = 0.007 and 0.013) and reduction of Streptococcus (p < 0.0001 and p < 0.0001) when compared to patients with VRL and control subjects, respectively. In addition, these patients had also significantly higher relative abundance of the genus Enhydrobacter (p = 0.029) and lower abundance of the genera Gemella (p = 0.002), Neisseria (p = 0.008), and Prevotella (p = 0.011) when compared to patients with VRL. We found only minor changes in the gut microbiota. Conclusion Our study, as the first one, highlighted significant differences in the composition of oral microbiota among patients with uveitis, VRL, and control subjects.